Determinan yang Berhubungan dengan Keberadaan Jentik di Kelurahan Rangkah Buntu Surabaya - Alivia Sasa Muda (Universitas Airlangga, 2019)
Background: Dengue Hemorrhagic Fever is still a problem in Indonesia. In 2016, the number of deaths in East Java due to dengue as much as 339 people or 1.4% of total patients. At the end of 2017, 4 cases of dengue fever were found in the RW.VI, Rangkah Buntu Village, Surabaya. One of the causes of dengue is the presence of larvae. Purpose: The purpose of this study to analyze the factors that affecting the presence of larvae in Rangkah Buntu Village. Methods: This research is an observational analytic research with quantitative approach. The study included cross sectional with a sample of 211 respondents. The sampling technique used is simple random sampling. The independent variables in this study were education, income, knowledge, attitude, 3M+, hanging dirty clothes for more than one day, draining the bath at least once a week and cleaning the house. And the dependent variable is the presence of larvae. Data collection techniques are divided into primary data (direct observation and questionnaire) and secondary data (journals and articles). Then the data were analyzed by chi square test with the help of SPSS program to see the influencing factor. Results: The results of this study indicate that the knowledge, activity of draining the bath tub at least once a week and hanging dirty clothes more than one day have an influence with the presence of larvae (chi square obtained p <α (α = 0,05)). Conclusion: There is no significant relationship between education, income, attitude, 3M +, and cleaning the house with the presence of larva in RW.VI area, Rangkah Buntu Village, Surabaya.